2016
DOI: 10.15244/pjoes/63672
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Urban Heat Island Using a Local Climate Zone Scheme

Abstract: IntroductionUrban heat island (UHI), a term first coined in the 1940s, refers to the atmospheric warmth of a city compared to the surrounding countryside. The amplitude of the UHI is usually expressed as the synchronous screen-height air temperature difference between urban and rural thermal sensors [1]. UHI is an unintended outcome of urbanization and this phenomenon occurs in almost all urban areas, which could also lead to increased energy demand and thermal discomfort [2]. Recognized causes of UHI are incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The highest LST is observed in high density residential area, commercial/Industrial service and public/educational institutions because its surface property is impervious with low albedo which store and emit more heat. The above result in consensus with the growing body of literature have revealed that LULC is directly associated with increase in (urban) LST and is a significant indicator and factor of UHI formation [37,40,41,42]. Finally, model validation was performed using the Root Mean Square Error (RMSE) method.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The highest LST is observed in high density residential area, commercial/Industrial service and public/educational institutions because its surface property is impervious with low albedo which store and emit more heat. The above result in consensus with the growing body of literature have revealed that LULC is directly associated with increase in (urban) LST and is a significant indicator and factor of UHI formation [37,40,41,42]. Finally, model validation was performed using the Root Mean Square Error (RMSE) method.…”
Section: Resultssupporting
confidence: 59%
“…It is evident from Figure 3 that the land surface temperature (LST) varies from one place to another within the metropolitan area, and some areas reflect high temperatures. The rising temperatures of some regions are mainly caused by the thermal property of building materials, dark surfaces with low albedo and urban geometry [36], anthropogenic heat production [37], and finally, the geographic location of the urbanized area [38]. The dip and spike in surface temperatures over water Journal of Management and Service Science (JMSS) A2Z Journals bodies show how water can maintains a fairly constant temperature, due to its high heat capacity [39].…”
Section: Resultsmentioning
confidence: 99%
“…The results from the mobile measurements will be used further to analyze the major urban drivers of UHI intensity in terms of LCZ type [8,52,57,63,[78][79][80][81][82][83][84], and associated impervious area fractions and aspect ratios [29,[85][86][87].…”
Section: Mobile Measurementsmentioning
confidence: 99%
“…Modified from Stewart & Oke (2012). Some studies divided meteorological sites into different LCZs based on field surveys (Fenner et al, 2014;Lehnert et al, 2015;Liu et al, 2018;Middel et al, 2014;Müller et al, 2014;Siu & Hart, 2013;Stevan et al, 2013;Stewart et al, 2014;Wang et al, 2016). The LCZ division through field surveys is time-consuming and laborious and can be hardly extended to LCZ mapping on the city scale.…”
Section: Introductionmentioning
confidence: 99%